Implementasi Aplikasi Sisdmk dalam Mewujudkan Ketenagaan di Puskesmas Tarogong Kabupaten Garut - Firman Sunarya; Nana Darna; Ferey Herman (Jurnal Manajemen Bisnis Digital Terkini, 2024)
The problems faced in this study include (1) How is the implementation of the SISDMK application in realizing manpower at the Tarogong Health Center, Garut Regency? (2) What are the obstacles in the implementation of the SISDMK application in realizing manpower at the Tarogong Health Center, Garut Regency? (3) What are the efforts to overcome the obstacles in the implementation of the SISDMK application in realizing manpower at the Tarogong Health Center, Garut Regency? This study aims to analyze descriptively (1) The implementation of the SISDMK application in realizing manpower at the Tarogong Health Center, Garut Regency. (2) Obstacles in the implementation of the SISDMK application in realizing manpower at the Tarogong Health Center, Garut Regency. (3) Efforts to overcome obstacles in the implementation of the SISDMK application in realizing manpower at the Tarogong Health Center, Garut Regency. The method used in this study is descriptive analysis with qualitative research design, while the technical data analysis, namely Data reduction, Data display, Triangulation and conclusion. The results of the study inform that (1) The implementation of the SISDMK application in realizing manpower at the Tarogong Health Center, Garut Regency as a whole has not been carried out properly. This is due to 4 dimensions, namely communication, resources, disposition and bureaucratic structure, which have been implemented well, namely communication, disposition and bureaucratic structure. While what has not been implemented well is resources. (2) Obstacles in implementing the SISDMK application in realizing manpower at the Tarogong Health Center, Garut Regency, namely the less than optimal competence of staff in operating SISDMK and the unavailability of sufficient and sustainable budget from the Health Center for the implementation of SISDMK.